RANCANG BANGUN APLIKASI KEPUASAN LAYANAN AKADEMIK BERBASIS MOBILE STUDI KASUS: UNIVERSITAS BUDI LUHUR - Subandi Subandi (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2018)
The development of technology, communication and information is an opportunity that can be used by institutions to produce quality information, quickly and easily obtained by anyone, especially their stakeholders. Institutions should take advantage of these technological advances to make it easier for their stakeholders to obtain information. Budi Luhur University is one of Education institution located in South Jakarta. Currently, complaint related to academic service is still done by providing criticism section and suggestion that limited only in working hours, so if stakeholders in this case the students want to submit complaints related to academic services submitted to the section of criticism and suggestions accommodated and then submitted to the management. Seeing these problems the authors intend to create a Design of Applications Satisfaction Mobile-Based by using PHP, API Server and Mysql Database. It is expected to help Budi Luhur University to get information from students related to the services provided. Complaint information from students can be received directly by the management, so action can be done quickly.